Agility in Indian manufacturing industries: an empirical investigation. (1st March 2012) - Saleeshya, P.G.; Subash Babu, A.; Vishnu, A.S.
This paper reports the salient details of a study carried out with the objectives of identifying what makes an organisation agile, identifying various enablers of agility by field study, developing a modelling framework for assessing agility and assessing agility in Indian manufacturing industries. For this purpose, data were collected from Indian manufacturing industries with the help of a questionnaire. The method of analytic hierarchy process was used to analyse and identify which among these factors are likely to have greater impact on realising an agile organisation. This study revealed a number of interesting observations, which are reported in this paper.